Relação entre capital social, compartilhamento de conhecimento, capacidades dinâmicas e desempenho organizacional - Nodari, Felipe (2017)
Academics points out Dynamic Capabilities as one of the most prominent theories in the strategic management field. This theory addresses how companies can achieve higher levels of organizational performance through the reconfiguration of their resources and capabilities. Despite its wide acceptance, researches on the subject still faces significant barriers: the lack of a valid and widely accepted measures due to uncertainties about its key concepts, and which contingencies affect the relationship between dynamic capacities and organizational performance. Dynamic capabilities are underpinned by knowledge resources, owned, or accessed by organizations, to explore opportunities and promote organizational reconfiguration. This study proposes that absorptive capacity, which focus on the evolution of the company's knowledge, complements the capacities of sensing, seizing and reconfiguring, as the dimensions of the dynamic capacities in an organization. In addition, it studies the relationship of internal and external social capital of organizations with dynamic capacities, mediated by the processes of sharing of interorganizational and intraorganizational knowledge, in order to elucidate the contribution of the knowledge from these two environments. Through a survey with 472 companies from Rio Grande do Sul, the model was validated with structural equation modeling. The results show that internal and external social capital, interorganizational and intraorganizational knowledge sharing, and dynamic capacities have a significant impact on organizational performance. Sharing knowledge with partner companies has greater influence on dynamic capabilities and performance than intraorganizational knowledge sharing, especially in dynamic environments. Regarding the four proposed dimensions for dynamic capacities, absorptive capacity precedes the capacities of sensing, seizing and reconfiguring, while detection enhances seizing opportunities and organizational reconfiguration. Looking for managerial contributions, this study proposes suggestions to facilitate the development of dynamic capabilities in organizations, which include the establishment of specific routines for sensing opportunities and threats, based on interorganizational relationships; the constitution of two distinct processes, one focused on taking advantage of the detected opportunities, and another, with a specific focus on organizational reconfiguration; the development of internal relations based on trust, common language and reciprocity facilitate the development of external relations; and the participation of individuals with different knowledge bases can enable the interpretation of opportunities in the external environment, contributing to their use on the organizational reconfiguration.